Comparison of Infraspinatus and Posterior Deltoid Muscle Activities According to Exercise Methods and Forearm Positions During Shoulder External Rotation Exercises - Myeong-gi Son; Suhn-yeop Kim (Korean Research Society of Physical Therapy, 2022)
Background: Shoulder external rotation exercises are commonly used to improve the stabi-lizing ability of the infraspinatus. However, during exercise, excessive activation of the poste-rior deltoid compared to the infraspinatus causes the humeral head to move anteriorly in an abnormal position. Many researchers have emphasized selective activation of the infraspina-tus during shoulder external rotation exercise.Objects: This study aims to delineate the optimal exercise method for selective activation of infraspinatus by investigating the muscle activities of the infraspinatus and posterior deltoid according to the four shoulder exercise methods and two forearm positions.Methods: Thirty healthy individuals participated in this study. The participants were instruct-ed to perform shoulder external rotation exercises following four exercise methods: sitting external rotation (SIER); standing external rotation at 90° abduction (STER); prone external ro-tation at 90° abduction (PRER); side-lying external rotation (SLER), and two forearm positions (neutral, supinated). The electromyography (EMG) signal amplitude was measured during each exercise. Surface EMG signals were recorded from the posterior deltoid, infraspinatus, and biceps brachii.Results: EMG results of the infraspinatus and posterior deltoid in PRER, were significantly higher than that of the other exercises (p < 0.01). The EMG ratio (infraspinatus/posterior deltoid) in SIER was significantly higher than that of the other exercises. EMG activation of the posterior deltoid in SIER, PRER, and SLER was significantly higher in neutral than in supinated (p < 0.01). Furthermore, the EMG of the infraspinatus in SIER was significantly higher in neu-tral than in supinated (p < 0.01). The EMG ratio (infraspinatus/ posterior deltoid) in SIER was significantly higher in neutral than in supinated (p < 0.05.) Contrarily EMG ratios in PRER and SLER were significantly higher in supinated than in neutral (p < 0.05).Conclusion: The results show that clinicians should consider these exercise methods and forearm positions when planning shoulder external rotation exercises for optimal shoulder rehabilitation.